1989
DOI: 10.1016/0035-9203(89)90632-9
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and Plasmodium falciparum infection in pregnant women in Kenya

Abstract: Women living under holoendemic conditions of malaria in Kenya exhibited an increased prevalence of clinical malaria during pregnancy. In addition parasite rate and density were higher in primigravidae compared to multigravidae. Higher serum cortisol concentrations were found in women with patent malaria during pregnancy and the levels were higher before, during and after the malaria episode. A causal relation between serum cortisol levels and suppression of malaria immunity during pregnancy is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 12 publications
4
26
1
1
Order By: Relevance
“…During normal labor, primiparous women have higher antepartem and early postpartum cortisol levels [20], but lower prolactin levels [21,22] than multiparous women. Vleugels et al reported that cortisol concentrations increase during the second trimester of pregnancy, with the highest levels in primigravidae and Plasmodium-infected women [23]. We recently confirmed this finding and found a positive correlation between cortisol concentration and parasite load at the time of delivery [13].…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…During normal labor, primiparous women have higher antepartem and early postpartum cortisol levels [20], but lower prolactin levels [21,22] than multiparous women. Vleugels et al reported that cortisol concentrations increase during the second trimester of pregnancy, with the highest levels in primigravidae and Plasmodium-infected women [23]. We recently confirmed this finding and found a positive correlation between cortisol concentration and parasite load at the time of delivery [13].…”
Section: Introductionsupporting
confidence: 64%
“…Cortisol and estrogens have been shown to depress the cellular immune response during pregnancy [12,13,32]. Vleugels et al reported that higher total cortisol levels cause loss of malaria immunity and that the serum concentration of total cortisol is higher in primigravidae than in multigravidae [23,33]. Prolactin might play a role in the T helper cell (Th1 and Th2) dysequilibrium observed in maternal malaria [34].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reduced responses to MalAg during acute infection (22) in malaria-exposed pregnant women compared to those in nonpregnant women (7,8,23) have been reported, with cytokine responses to mitogens in some cases being relatively preserved (7,22,23). The mechanisms by which this outcome occurs are likely to be complex, perhaps involving parasite-induced cytokine dysregulation (2) and disruption of antigen presentation or dendritic cell function (34) and, in pregnant women, hormones (3,35). It will be necessary to perform intensive functional and mechanistic studies to identify the important players and their respective roles in malaria-associated immune modulation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, increased serum cortisol levels are observed in pregnancy, being highest in primigravid women in areas of malaria transmission [23,143,194], but these differences are not marked and the progressive increase in cortisol during pregnancy does not correspond to the prevalence of malaria which peaks or plateaus in the second trimester. Increased cortisol levels were associated with malaria during pregnancy in a Kenyan study [194], and because primigravidae are infected most frequently this may confound studies that compare cortisol levels between parity groups. Similar associations were found in P. berghei-infected pregnant mice [191].…”
Section: Changes In Cellular Immune Function During Pregnancy and Susmentioning
confidence: 93%